Corporate restructuring during performance declines in Japan - Kang, Jun-Koo; Shivdasani, Anil (Journal of Financial Economics, 1997)
This paper documents the restructuring of 92 Japanese corporations that experienced a substantial decline in operating performance between 1986 and 1990. These firms implement a number of downsizing measures such as asset sales, plant closures, and employee layoffs. Firms also expand and diversify, and often restructure their internal operations. Compared to US firms with a similar decline in performance, however, Japanese firms are less likely to downsize, and layoffs affect a smaller fraction of their workforce. The frequency of asset downsizing and layoffs in Japanese firms increases with the ownership by the firm's main bank and other blockholders. Blockholders also increase the probability of management turnover, outside director removals and outside director additions, but decrease the likelihood of acquisitions. We document improvements in operating performance following downsizing actions in Japan.